PENGARUH GOOD PUBLIC GOVERNANCE (GPG) TERHADAP KUALITAS INFORMASI LAPORAN KEUANGAN PEMERINTAHAN DESA DI KABUPATEN KEDIRI - Anas, M.; Forijati, Rr.; Muchson, Mochamad (UNIVERSITAS NUSANTARA PGRI KEDIRI, 2021)
The purpose of village development in achieving the welfare of the village community requires a good village governance in carrying out public services. The implementation of quality village government will create an orderly life of government and society and will realize the expected good public governance (GPG). One form of service output that reflects government performance which is also an instrument of government accountability to stakeholders is financial reports. Quality village financial reports are information that can present honestly, truthfully, relevantly, reliably, can be compared, and can be understood by all parties related to the financial statements. The research objective was to test empirically and to analyze the effect of GPG on the quality of information on village government financial reports in Kediri Regency. The research sample was 52 villages in Kediri Regency with respondents who were managers of village financial reporting. The research data were obtained through an instrument in the form of a questionnaire. Hypothesis testing is carried out by multiple linear regression analysis using the SPSS V.23 application. The results of data analysis prove that the accountability and fairness variables and equality variables have a significant effect on the quality information of village financial report, while the variables of democracy, transparency, and legal culture have no significant impact on the quality information of village government financial reports.